Hak Disabilitas Dalam Aksesibilitas Ruang Publik Di Kota Surabaya - Puspita, Amelia; Soeskandi, Hari (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2022)
The purpose of this research is to find legal certainty related to not being fully guaranteed regarding disability rights in the city of Surabaya. By using a normative research method which is by reviewing the regulations regarding accessibility rights for people with disabilities in the city of Surabaya. Through the concept that the researcher created, the researcher wants to describe and describe the meaning of legal certainty on accessibility rights for persons with disabilities, which refers to the role of the Surabaya city government and the absence of sanctions for the government as the implementer and organizer of the procurement of accessibility rights for persons with disabilities. The problem regarding accessibility rights for persons with disabilities lies in the uneven implementation of accessibility rights for persons with disabilities in the city of Surabaya, where the development of accessibility for persons with disabilities is only found in certain places such as; Education Museum, Al-Akbar Mosque, Gubeng Kertajaya Sidewalk, City Government Building, and Talking Park. Which can be seen that disability in the city of Surabaya is not only located in the city center but throughout the city of Surabaya, including the suburbs. Keywords: Disability, Accessibility, Public Spatial Planning